Lithuania : History and Future of the Currency Board Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
The paper examines the evolution of the institutional setup of Lithuania's Currency Board Arrangement (CBA) and competitiveness from 1994 through 2001, with a view to determining the resilience of the Lithuanian CBA to external shocks in 2002-03. First, several indicators of competitiveness are analyzed in the context of productivity gains and flexibility of the labor market and prices are considered. Then, the equilibrium exchange rate and misalignments of the actual rate from it are estimated in a cointegration framework. The paper concludes that, under current policies, the CBA would be able to cope with sizable external shocks during 2002-03 provided supporting policies remain in place.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet